2011
DOI: 10.1080/02705060.2011.559745
|View full text |Cite
|
Sign up to set email alerts
|

Growth response to temperature and light inNostoc spongiaeforme(Cyanobacteria)

Abstract: Cyanobacteria and algae are problematic in California rice fields that are typically shallow and have high nutrient levels, providing ideal growing conditions. Nostoc spongiaeforme is a problem because extensive floating mats dislodge rice seedlings or smother them when the mats accumulate in windward areas. There is little published information on growth requirements for N. spongiaeforme. We grew N. spongiaeforme in BG-11 medium at 24 combinations of light (22, 87, 162, and 400 mM m À2 s À1 ) and temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This is in accordance with the results shown by Spencer et al (2011), in which growth of Nostoc spongiaeforme increased up to 227 µE/m 2 s (similar to L3 in this study). Initial and final TIN concentrations in the growth media of Nostoc sp.…”
Section: Nostoc Spsupporting
confidence: 93%
“…This is in accordance with the results shown by Spencer et al (2011), in which growth of Nostoc spongiaeforme increased up to 227 µE/m 2 s (similar to L3 in this study). Initial and final TIN concentrations in the growth media of Nostoc sp.…”
Section: Nostoc Spsupporting
confidence: 93%
“…The optimum growth condition for the selected bluegreen alga was achieved at temperature of 25°C which is similar to the finding of Li-Juan et al (2011) on Nostoc commune. Spencer et al (2011) found optimum growth of Nostoc spongiaeforme at 26°C on BG-11 medium.…”
Section: Temperaturementioning
confidence: 83%
“…The optimal average light intensity for H 2 production in Chlamydomonas reinhardtii was found by Laurinavichene et al (2004) . But Spencer et al (2011) found that 227 µEm -2 s -1. of light was optimum for the growth of Nostoc spongiaeforme on BG-11 medium. The reason behind this might be the variation among the growth media.…”
mentioning
confidence: 99%
“…The typical growth rate of Nostoc is 30 days (Spencer et al 2011 ) and Chlorella is 7 days (Gitau et al 2021 ). Therefore, the sampling frequency for both microalgae strains was decided at 3-day intervals for Nostoc and 24-h intervals for Chlorella .…”
Section: Methodsmentioning
confidence: 99%